FEATURES AND KEY ELEMENTS OF SERVICE ACTIVITIES IN THE AVIATION INDUSTRY - Dokiienko, L. M.; LyamzinА. О. (Systems and Technologies, 2023)
The article proves that a well-built service system in the modern aviation industry is of primary importance. The essence and features of service activities in the aviation industry are substantiated: direct contact and interaction between the consumer and the service provider at all stages in the B2C and B2B segment; high role of personnel; individual approach to clients; special attention to customer experience; maintaining the quality of services; wide application of technologies; result orientation; mandatory provision of aviation security; presence of non-standard situations; convenience and technical adequacy of services; balanced pricing policy; high requirements for the completeness and quality of passenger information provision. It is proposed to consider service activity in the aviation industry in the context of a client-oriented approach to service in terms of two components: the passenger service system and the service system for the production infrastructure of the airport and airlines at the airport. The passenger service system is proposed to include: the construction of customer-oriented service and the use of modern technologies of service and communication with customers for high-quality passenger service by airport and airline personnel. The components of the assessment of service quality at the airport are defined as premises/infrastructure, processes, and personnel, for which a system of assessment criteria has been developed. The assessment of passenger service by the airline is proposed to be carried out in terms of ground service, which includes pre-flight and post-flight passenger service and organization of aviation activities; and passenger service on aircraft board with evaluation of the efficiency of the cabin crew and the on-board product. An extended system of evaluation criteria has been developed for each component. The service system of the production infrastructure of the airport and airlines at the airport includes: services of handling companies, services for the operation and maintenance of the airfield, services for the organization of flight support and air cargo and baggage delivery services. For each component, the types of services that form them are considered.